Cardiorespiratory responses to exercises of equal relative intensity distributed between the upper and lower body - Faria, E. W.; Faria, I. E. (Journal of Sports Sciences, 1998)
The principles underlying the cardiorespiratory responses to upper body versus lower body exercise remain unclear. We explored the hypothesis that workloads of the same percentage of maximum strength for a particular part of the body might elicit similar cardiovascular responses. Twelve trained female university rowers (mean +/- s: age, 22.8 +/- 1.3 years; body mass, 66.9 +/- 1.8 kg; height, 169 +/- 6 cm; body fat, 18 +/- 2%; HRpeak, 190 +/- 3 beats min(-1); VO2 peak, 50.7 +/- 2.6 ml kg(-1) min(-1)) performed four 12 min exercise trials on a rowing ergometer. Arm rowing, leg extension and arm rowing + leg extension workloads were set at 20% of the mean of their respective three-repetition maximum (3-RM). The combination of arm rowing and leg extension was also performed in a reciprocal workload fashion; that is, the arm workload was 20% of the mean 3-RM for leg extension, and the leg extension workload was 20% of the mean 3-RM for arm rowing. Analysis of variance and Tukey HSD showed that, although the power output for leg extension was 144% higher than for arm rowing, the mean VO2, VE and heart rate values were not significantly different between exercise modes. Oxygen uptake for reciprocal arm rowing + leg extension, with the arms performing 71% of the total power output, was not significantly different from non-reciprocal arm rowing + leg extension; however, the VE and heart rate values were higher. Our results suggest that, during submaximal exercise, cardiorespiratory responses to upper body exercise do not differ significantly from those to lower body exercise, so long as the upper and lower body workloads are set at an equal relative strength level.